Functional evaluation instruments in patients with chronic obstructive pulmonary disease: a review of the literature - Moreira, Fabiana Barroso Rocha; Panka, Gisele Fernanda de Lucena; Vieira, Danielle Soares Rocha; Faria, Luísa Martins; Velloso, Marcelo (Journal of Respiratory and CardioVascular Physical Therapy, 2013)
Background: COPD is a disabling disease that causes dyspnea and physical fatigue, affecting the activities of daily living (ADL). Objective: To detect, through a literature review, the main tools used to evaluate functioning of patients with COPD and to determine the most widely used test in clinical practice and scientific research. Methods: A literature search was conducted in Medline, Lilacs and SciELO covering the period from 1992 to 2011 and studies were selected for posterior analysis, according to pre-established criteria. Results: 53 articles on the functioning of patients with COPD were found, 22 specifically addressing the creation and/or implementation of clinical tests or functional assessment questionnaires. Five questionnaires and four clinical trials were found, all with good psychometric properties. Conclusion: The main instruments were: London Chest Activity of Daily Living Scale (LCADL), Pulmonary Function Status and Dyspnea Questionnaire (PFSDQ), Pulmonary Functional Status Scale (PFSS), Human Activity Profile (HAP), Manchester Respiratory Activities of Daily Living Questionnaire, Glittre ADL-test, Shuttle Test (ST), 6-minute walk test (6MWT) and the Sit-to-stand test (STST). The most commonly used test was the 6MWT, which is also often used as a parameter to correlate and validate other tests and questionnaires.